2021
DOI: 10.1089/jpm.2020.0218
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in Potentially Inappropriate Interventions in Trauma Patients following a Palliative Care Consultation

Abstract: Background: Palliative care is expanding as part of treatment, but remains underutilized in trauma settings. Palliative care consultations (PCC) have shown to reduce nonbeneficial, potentially inappropriate interventions (PII), as decision for their use should always be made in the context of both the patient's prognosis and the patient's goals of care. Objective: To characterize trauma patients who received PCC and to analyze the effect of PCC and do-notresuscitate (DNR) orders on PII in severely injured pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…Multidisciplinary family conferences were associated with higher institution of comfort measures, and code status deescalation occurred earlier with early family meetings 39 . Finally, a 2020 study showed that the majority of invasive procedures had already been undertaken before PC consultation, which occurred at a mean time of 5.3 days after hospital admission 12 …”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Multidisciplinary family conferences were associated with higher institution of comfort measures, and code status deescalation occurred earlier with early family meetings 39 . Finally, a 2020 study showed that the majority of invasive procedures had already been undertaken before PC consultation, which occurred at a mean time of 5.3 days after hospital admission 12 …”
Section: Discussionmentioning
confidence: 99%
“…39 Finally, a 2020 study showed that the majority of invasive procedures had already been undertaken before PC consultation, which occurred at a mean time of 5.3 days after hospital admission. 12 Therefore, 5 days after injury appears to be too late, and 3 days is the most frequently reported recommendation for integration of PC specialists, particularly in the ICU. 40 The delay to PC consultation, given the mean time to consult of 6.83 days in our study, is consonant with a recent qualitative study describing the adoption of concordant PC by ICU physicians, as representative of what they deemed the "nascent" phase of expert PC incorporation, possibly because of "a perception that there's nothing that a palliative care physician can do that an ICU physician can't do."…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations